PENGEMBANGAN MODEL LATIHAN RENANG GAYA BEBAS PADA ATLET PEMULA UMUR 6-12 TAHUN DI HBSC DHARMASRAYA BERBASIS MEDIA - Ratu Munawaroh; Zuhar Ricky; Maldin Ahmad Burhan (Dharmas Journal of Sport, 2023)
The research problem is that there are several groups for beginners who have a lot ofdeficiencies when doing freestyle swimming, and swimmers also easily feel fatigue when doing startsand turning while swimming. So in this study a freestyle swimming training model was developed.The purpose of this research is to develop a freestyle swimming training model, so it is hoped thatthe training model developed by the researchers can help swimmers not get bored doing freestyleexercises. This type of research is Research and Development (R & D). Model development uses theADDIE model which consists of 5 stages, namely analysis, design, development, implementation andevaluation stages. The results of the research on developing freestyle swimming training models forbeginners in the validity test obtained percentage data with an average of 85.13% categorized asvery valid, practicality tests by swimming coaches with a percentage of 93.33% and beginnerathletes with a percentage of 83.71% categorized very practical, while the effectiveness test with apercentage of 86% is categorized as very effective. Based on the results that have been obtained, thefreestyle swimming training model development model for beginners is categorized as valid,practical and effective.